Percutaneous device closure of persistent ductus venosus presenting with hemoptysis - Venkateshwaran Subramanian; Mahadevan Krishnamoorthy Kavassery; Sivasankaran Sivasubramonian; Bijulal Sasidharan (Wolters Kluwer Medknow Publications, 2013)
An eight-year-old boy was evaluated for unexplained hemoptysis and cyanosis. A contrast echocardiogram was suggestive of pulmonary arteriovenous fistula. Further evaluation revealed persistent ductus venosus (PDV) and aortopulmonary collaterals. Both the PDV and aortopulmonary collaterals were closed percutaneously. PDV is amenable for device closure after detailed anatomical evaluation. Prior to closure, it is important to ensure adequate portal vein arborization into the liver and normal portal pressure after test balloon occlusion.